A method for changing single difference WL-FCB to un-difference WL-FCB and the analysis of temporal variation characteristics. Issue 2 (4th May 2021) - Yue, Caiya; Dang, Yamin; Xu, Changhui; Gu, Shouzhou; Wang, Min; Dai, Huayang
ABSTRACT: In this paper, a rank deficient adjustment model with inequality constrained is implemented to realise the conversion from the single-difference (SD) wide lane fractional cycle bias (WL-FCB) to undifferenced(UD) WL-FCB. The results are compared with the un-differential FCB published by Centre National d'Etudes Spatiales (CNES), and the temporal variation characteristics of SD WL-FCB and UD WL-FCB are analysed. The results indicate that the stability of the daily WL-FCB, whether it is SD or UD, is better than that of an hour. The UD WL-FCB recovered by using the above approach is compared with CNES, and it is found that the difference between (−0.06 0.06) cycles are more than 90%. The fixing success rate of the WL ambiguity from DOY 240 to 250 of 2017 is calculated by using probability function, which shows that fixed success rate is over 79% for all satellites, and the average is about 88%.